Effects of partial hepatectomy on plasma fibronectin concentrations in the rat. - Nilsson, T. K. (1987)
Rats were subjected to 60% partial hepatectomy. In the immediate postoperative period, there was a small decline in plasma fibronectin concentrations, which was normalized already 12 h post-operatively. Metabolic labelling of fibronectin with 35S-methionine showed that the rate of incorporation of label was unchanged after partial hepatectomy. However, when the abdominal viscera were excluded from the circulation, no incorporation of label was found. These results show that the rate of fibronectin biosynthesis has the rapid regulation characteristics of an acute phase reactant. Peripheral tissues do not contribute significantly to the plasma fibronectin concentration. Intra- or retro-peritoneal viscera, most likely the liver, are responsible for the synthesis of rat plasma fibronectin.